Os direitos humanos à água e ao saneamento: repercussões jurídicas na gestão de recursos hídricos e saneamento no direito brasileiro e emergência de uma organização sul-americana de gestão de águas - Melo, Álisson José Maia (2018)
The United Nations General Assembly declaration recognizing human rights to clean and safe drinking water and sanitation through Resolution 64/292 is the result of a long process of evolution of international freshwater law. The legal repercussion of this declaration for the management of water resources and for the provision of public basic sanitation services in Brazilian law is the object of this research, made from a deductive method, with an institutional approach under the paradigm of complexity. Taking the statement seriously, and its normative force as a result of the 1966 International Covenant on Economic, Social and Cultural Rights, the internalization into national legal systems of the human rights to safe drinking water and basic sanitation, with the necessary protection of the sources of water to ensure its drinkability, with the status of international standards, should lead to a change of culture and of legal interpretation. After a review of the Brazilian legislation on water resources and basic sanitation services, points of conflict with the human rights in question are identified, developing systematic and coherent interpretations of the national legal system. Next, recognizing that the normative force of these human rights leads to States' duty to ensure efficiency in both water management and water and sanitation services, these rights will suggest the need for regional integration for protection of water sovereignty in the face of the global crisis of water scarcity. In this sense, the research cut focuses on South America, since the great Brazilian watersheds are confined in this subcontinent. To that end, it is necessary to investigate whether national laws and regional agreements are compatible with the construction of a regional model of South American water and sanitation management. Once analyzed and discussed the national legislations and experiences of multilateral cooperation in the major South American river basins, the Latin American integration processes are critically analyzed, proposing reasons for their failure. However, it is understood that the model of the Union of South American Nations seems to be better suited to the common tradition of the region and would be an appropriate paradigm for the development of water and sanitation management focused primarily on social and environmental aspects. Four proposals for South American integration for water and sanitation management are presented and a basic principles for the constitution of this international organization is summarized.